The role of pre-emptive Transjugular Intrahepatic Portosystemic Shunt in acute variceal bleeding: a literature review - Charelle Manning; Amera Elzubeir; Syed Alam (SAGE Publishing, 2021)
The development of portal hypertension has serious implications in the natural history of liver cirrhosis, leading to complications such as ascites, hepatic encephalopathy and variceal bleeding. The management of acute variceal bleeding has improved in the last two decades, but despite the advances in endoscopic methods the overall prognosis remains poor, particularly within a subgroup of patients with more advanced disease. The role of Transjugular Intrahepatic Portosystemic Shunt (TIPSS) is a well-established method of achieving haemostasis by immediate portal decompression; however, its use in an emergency setting as a rescue strategy is still associated with high mortality. It has been shown that 'early' use of TIPSS as a pre-emptive strategy in a patient with acute variceal bleed in addition to the standard of care confers superior survival outcomes in a subgroup of patients at high risk of treatment failure and death. The purpose of this review is to appraise the literature around the indications, patient selection, utility, complications and economic considerations of pre-emptive TIPSS.